Insights into the regulation of energy metabolism during the seed-to-seedling transition in marine angiosperm Zostera marina L.: Integrated metabolomic and transcriptomic analysis - Zhu, Meiling; Zang, Yu; Zhang, Xuelei; Shang, Shuai; Xue, Song; Chen, Jun; Tang, Xuexi (Frontiers in Plant Science, 2023)
Seed development is a crucial phase in the life cycle of seed-propagated plants. As the only group of angiosperms that evolved from terrestrial plants to complete their life cycle submerged in marine environments, the mechanisms underlying seed development in seagrasses are still largely unknown. In the present study, we attempted to combine transcriptomic, metabolomic, and physiological data to comprehensively analyze the molecular mechanism that regulates energy metabolism in Zostera marina seeds at the four major developmental stages. Our results demonstrated that seed metabolism was reprogrammed with significant alteration of starch and sucrose metabolism, glycolysis, TCA cycle, and the pentose phosphate pathway during the transition from seed formation to seedling establishment. The interconversion of starch and sugar provided energy storage substances in mature seeds and further acted as energy sources to support seed germination and seedling growth. The glycolysis pathway was active during Z. marina germination and seedling establishment, which provided pyruvate for TCA cycle by decomposing soluble sugar. Notably, the biological processes of glycolysis were severely inhibited during Z. marina seed maturation may have a positive effect on seed germination, maintaining a low level of metabolic activity during seed maturation to preserve seed viability. Increased acetyl-CoA and ATP contents were accompanied with the higher TCA cycle activity during seed germination and seedling establishment, indicating that the accumulations of precursor and intermediates metabolite that can strengthen the TCA cycle and facilitate energy supply for Z. marina seed germination and seedling growth. The large amount of oxidatively generated sugar phosphate promotes fructose 1,6-bisphosphate synthesis to feed back to glycolysis during seed germination, indicating that the pentose phosphate pathway not only provides energy for germination, but also complements the glycolytic pathway. Collectively, our findings suggest these energy metabolism pathways cooperate with each other in the complete process of seed development, transforming seed from storage tissue to highly active metabolic tissue to meet the energy requirement seed development. These findings provide insights into the roles of the energy metabolism pathway in the complete developmental process of Z. marina seeds from different perspectives, which could facilitate habitat restoration of Z. marina meadows via seeds.